Phase II study of gefitinib in patients with advanced salivary gland cancers. Issue 5 (30th March 2015) - Jakob, John A.; Kies, Merrill S.; Glisson, Bonnie S.; Kupferman, Michael E.; Liu, Diane D.; Lee, J. Jack; El‐Naggar, Adel K.; Gonzalez–Angulo, Ana M.; Blumenschein, George R.
Abstract: Background: The purpose of this study was to determine the antitumor activity of the epidermal growth factor receptor (EGFR) inhibitor gefitinib in patients with recurrent/metastatic salivary gland cancer. Methods: We conducted a phase II study in adenoid cystic carcinoma (ACC) and non‐ACC. Gefitinib was administered 250 mg orally daily. The primary endpoint was tumor response. Secondary endpoints included progression‐free survival (PFS), overall survival (OS), and disease control rates. EGFR and human epidermal growth factor receptor 2 (HER2) expression were evaluated and correlated with outcomes. Results: Thirty‐seven patients were enrolled in this study, and 36 were evaluable (18 with ACC and 18 with non‐ACC). No responses were observed. Median PFS was 4.3 months and 2.1 months, and median OS was 25.9 months and 16 months for patients with ACC and non‐ACC, respectively. The disease control rate at 8 weeks was higher in patients with ACC. No unexpected toxicities occurred. EGFR and HER2 overexpression did not correlate with outcomes. Conclusion: We did not observe significant clinical activity of gefitinib in advanced salivary gland cancer. NCT00509002. © 2015 Wiley Periodicals, Inc. Head Neck 37: 644–649, 2015